Synthesis of waterborne acrylic copolymer resin as a binding agent for the development of water‐based inks in the printing application. Issue 5 (18th March 2021) - Sharma, Bhavna; Sauraj, Singh; Kumar, Bijender; Pandey, Arun; Dutt, Dharm; Negi, Yuvraj Singh; Maji, Pradip K.; Kulshreshtha, Anurag
Abstract: In this study, a new waterborne acrylic copolymer resin (acrylic‐ co ‐resin) was synthesized to develop water‐based printing inks on polyester (PET) film. The synthesized acrylic resin showed good water solubility, high acid value (120 mg KOH/g), about 57% solid content. The developed water‐based inks (cyan, magenta, and yellow) exhibited small particle size (<1 μm) and optimum surface energy within required values (31.5, 32, and 30 mN/m) for good adhesion of ink upon PET films. The developed inks also showed good storage stability for 30 days. Further, to evaluate the application performance, the inks were printed on corona‐treated PET films at room temperature, and the ink drying time was measured. Further, the inks were printed on the corona‐treated PET film to evaluate the application performance. The developed inks showed a short drying time (7–9 s), which indicates their fast drying nature. Moreover, the developed inks showed good printability, color strength, high adhesion, and excellent rub‐resistant properties. Thus, the overall results demonstrated the potential of water‐based inks in printing applications. Abstract :